Reaction of tetrathiafulvalene derivative with vanadyl (VO2+) - Ibasco, Reynaldo R. (Animo Repository, 2002)
A TTF derivative, 5, (2,3-bis (2-cyanoethylthio)-6,7-ethylenethio TTF) was synthesized, deprotected and reacted with VOSO43H20 following established procedure. The methanol extract of the crude mixture was found to give a greenish-blue needlelike crystal after standing overnight. IR data revealed complete deprotection and UV-Vis results showed a coordination of the VO2+ ion with the organic ligand as evidenced by the presence of a band due to a charge transfer between metal and the ligand. The ESI-MS data point to a most likely structure for the complex with a 2:1 ligand to metal ratio. This compound is the first reported TTF-dithiolate complex with VO2+.